2017
DOI: 10.2105/ajph.2017.303934
|View full text |Cite
|
Sign up to set email alerts
|

Community Health Worker Impact on Chronic Disease Outcomes Within Primary Care Examined Using Electronic Health Records

Abstract: Although patients' chronic disease indicators consistently improved, between-group models provided no additional evidence of impact. EHRs' evolution may elucidate CHW contributions moving forward.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 29 publications
1
26
0
Order By: Relevance
“…While there was a large range in the ages of the patients in the included articles, age acts as a confounder in the perception of technology, with older generations often being averse to technology [60]. Lastly, while it would have been ideal to include views of all stakeholders involved, we were unable to find opinions from patients' caregivers, family members, community health workers and their families, hospital administrators, funders and legislators, even though they play an integral role in the education and care of a person with diabetes [67,68].…”
Section: Limitationsmentioning
confidence: 99%
“…While there was a large range in the ages of the patients in the included articles, age acts as a confounder in the perception of technology, with older generations often being averse to technology [60]. Lastly, while it would have been ideal to include views of all stakeholders involved, we were unable to find opinions from patients' caregivers, family members, community health workers and their families, hospital administrators, funders and legislators, even though they play an integral role in the education and care of a person with diabetes [67,68].…”
Section: Limitationsmentioning
confidence: 99%
“…By assuming a broad range of responsibilities, CHWs bridge the gap between primary care provision and well-being outside the clinical setting, particularly among patients most in need. Several studies have demonstrated reductions in care utilization and more equitable access to curative services for vulnerable patients managing chronic health conditions when CHWs were included in the patient's care team ( [10][11][12][13]; Moffett M, Kaufman A, & Bazemore, 2019 [14];). One randomized control trial of CHWs supporting low-income patients with multiple chronic conditions demonstrated improvements in health outcomes, mental health, and reductions in hospitalizations [7].…”
Section: Introductionmentioning
confidence: 99%
“…As clinics are increasingly integrating the CHW workforce into primary care, it is crucial to ensure that effective and evidence-based CHW community interventions are available to complement clinic efforts. Researchers have sought to delineate the most important and effective roles of CHWs within the clinical setting [31, 32]. Clinic-based CHWs work with patients to support them in disease self-management, navigation of health and social systems, and in health education.…”
Section: Introductionmentioning
confidence: 99%